The motorcycle diaries : notes on a Latin American journey - Guevara, Che, 1928-1967. (London : Harper Perennial, 2004)
Latin American revolutionary Che Guevara chronicles his 1952 adventure on motorbike throughout South America with friend Alberto Granado, during which he came face-to-face with the realities of poverty throughout the continent.
"Also published in Spanish as 'Diario de Motocicleta'."
Translation of: Notas de viaje.
Adult.
Adult
Keywords: Granado, Alberto, -- 1922-2011 -- Travel -- South America; Guevara, Che, -- 1928-1967 -- Travel -- South America; Granado, Alberto, -- 1922-2011 -- Travel; Guevara, Che, -- 1928-1967 -- Travel; South America -- Description and travel; South America -- Social conditions -- 20th century; South America -- Description and travel; South America -- Social conditions